Resource Rents, Coercion, and Local Development : Evidence from Post-Apartheid South Africa - Bottan, Nicolas Luis; Bastos, Paulo; Bottan, Nicolas (World Bank, Washington, DC, 2016)
This paper examines how the dismantling of coercive institutions associated with the end of apartheid in South Africa in 1994 affected the distribution of rents from natural resource exports. It identifies the interplay between coercive institutions and natural resource rents as an important driver of local development. Using data from the 1996 census, the paper documents large income gaps between communities located just-inside and just-outside the former self-governing territories set aside for black inhabitants. Examining relative changes between 1996 and 2011, the paper finds that spatial income convergence was considerably stronger among marginalized communities with higher initial exposure to resource rents. These results accord with standard bargaining theory in which the dismantling of coercive institutions improves the negotiating position of unionized workers in the mining industry.